Multifaceted Function of Myosin-18, an Unconventional Class of the Myosin Superfamily - Ouyang, Zhaohui; Zhao, Shuangshuang; Yao, Su; Wang, Jing; Cui, Yanqin; Wei, Ke; Jiu, Yaming (Frontiers in Cell and Developmental Biology, 2021)
Myosin is a diverse superfamily of motor proteins responsible for actin-based motility and contractility in eukaryotic cells. Myosin-18 family, including myosin-18A and myosin-18B, belongs to an unconventional class of myosin, which lacks ATPase motor activity, and the investigations on their functions and molecular mechanisms in vertebrate development and diseases have just been initiated in recent years. Myosin-18A is ubiquitously expressed in mammalian cells, while myosin-18B shows strong enrichment in striated muscles. Myosin-18 family is important for cell motility, sarcomere formation and mechano-sensing, mostly by interacting with other cytoskeletal proteins and cellular apparatus. Myosin-18A participates in several intracellular transport processes, such as Golgi trafficking, and has multiple roles in focal adhesions, stress fibers and lamellipodia formation. Myosin-18B, on the other hand, participates in actomyosin alignment and sarcomere assembly, thus relating to cell migration and muscle contractility. Mutations of either Myo18a or Myo18b cause cardiac developmental defects in mouse, emphasizing their crucial role in muscle development and cardiac diseases. In this review, we revisit the discovery history of myosin-18s and summarize the evolving understanding of the molecular functions of myosin-18A and myosin-18B, with an emphasize on their separate yet closely related functions in cell motility and contraction. Moreover, we discuss the diseases tightly associated with myosin-18s, especially cardiovascular defects and cancer, as well as highlight the unanswered questions and potential future research perspectives on myosin-18s.